Video Strategy as Scaffolding to Foster Students’ Grammar Proficiency and Writing Skills in EFL Learning - Leona Patria Devi; M. Zaenal Abidin; Yuyun Yulia; Roi Boy Jon; Soni Ariawan; Rangga Alif Faresta; Siti Hanum Afuwani (Journal of Languages and Language Teaching, 2024)
Despite its significance particularly when it comes to writing competence, numerous studies have revealed that grammar is still considered complicated to grasp and used by students. The purpose of this study was to determine how video-based instruction affects students' understanding of grammar in writing assignments. This sequential explanatory mixed-method study aimed to investigate how students' grammatical skills especially in degree of comparison might be improved. Quantitative evaluations such as creating written test materials for the students and qualitative interviews with both teachers and students were employed. The findings showed that students' comprehension of grammatical rules for statistical tests had improved. Descriptive data evidenced that the students were clearly excited, enthralled, and actively involved with the tactics; served as a scaffold to lower obstacles; enhanced language learners' understanding; and increased students' vocabulary. Both quantitative and qualitative approaches evidenced the significance of implementing English videos to promote students’ grammatical competence in writing skills. The study's implications and suggestions are discussed.